Customer Perception of Forensic Accounting and Corporate Framing in the Use of Digital Banking - Fatmawati Fatmawati; Harti Budi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Digital banking technology become a new challenge in the banking industry that require rapid development, either at the service level that directly affects customer satisfaction or the risk assessment that inherently occurred. This study aims to examine the effect of customer perception on Forensic Accounting and Corporate Framing in the use of Digital Banking by comparing the differences in customers’ backgrounds based on their profession. This research is quantitative research with a comparative study method where participants are arranged into 2 groups based on their professional background. The participants were selected using the purposive sampling method and analyzed using the independent t-test. The results showed that although customers in both groups showed the same sensitivity to the preference of digital banking facilities, customers with an accountant background were likely to be more selective in choosing digital banking.